A bibliometric analysis of perioperative rehabilitation research between 2005 and 2024 - Li, Juan; Su, Fen; Zhang, Qing; Song, Guiqi (Frontiers in Rehabilitation Sciences, 2025)
Effective rehabilitation can improve the prognosis of surgical patients, thereby enhancing their medical experience. In recent years, relatively more research is been carried out in this field; therefore, it is necessary to use bibliometric analysis to understand the development status and main research hotspots of perioperative rehabilitation, so as to determine the role of rehabilitation in the perioperative period. All documents related to perioperative rehabilitation and published from 2005 to 2024 were retrieved from the Web of Science Core Collection (Woscc). Number of articles, countries/regions, institutions, journals, authors, and keywords were analysed using VOSviewer and CiteSpace. A total of 829 studies on perioperative rehabilitation were included in the bibliometric analysis. The number of articles has steadily and rapidly increased since 2016. Over time, the publication outputs increased annually. There are 532 keyword nodes in total, of which the five keywords that appear most frequently are “surgery” “rehabilitation” “Outcome” “management” and “complications”. Research on the perioperative rehabilitation has developed rapidly. This study provides necessary information for researchers to understand the current status, collaborative networks, and main research hotspots in this field. In addition, our research findings provide a series of recommendations for future studies.